Should cyclosporine be useful in renal transplant recipients affected by SARS‐CoV‐2?. Issue 11 (17th July 2020) - Rodriguez‐Cubillo, Beatriz; de la Higuera, Maria Angeles Moreno; Lucena, Rafael; Franci, Elena V.; Hurtado, Maria; Romero, Natividad C.; Moreno, Antolina R.; Valencia, Daniela; Velo, Mercedes; Fornie, Iñigo S.; Sanchez‐Fructuoso, Ana I.
Abstract : Minimization of immunosuppression and administration of antiretrovirals have been recommended for kidney transplant recipients (KTRs) with coronavirus disease 2019 (COVID‐19). However, outcomes remain poor. Given the likely benefit of cyclosporine because of its antiviral and immunomodulatory effect, we have been using it as a strategy in KTRs diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). We studied 29 kidney transplant recipients (KTRs) who were admitted to our institution with COVID‐19 between March 15and April, 24, 2020. Mycophenolate and/or mammalian target of rapamycin inhibitors (mTORi) were discontinued in all patients. Two therapeutic strategies were compared: Group 1, minimization of calcineurin inhibitors (N = 6); and Group 2, cyclosporine‐based therapy (N = 23), with 15 patients switched from tacrolimus. Hydroxychloroquine was considered in both strategies but antivirals in none. Six patients died after respiratory distress (20.6%). Five required mechanical ventilation (17.2%), and 3 could be weaned. Nineteen patients had an uneventful recovery (65.5%). In group 1, 3 of 6 patients died (50%) and 1 of 6 required invasive mechanical ventilation (16.7%). In group 2, 3 of 23 patients died (12.5%). Renal function did not deteriorate and signs of rejection were not observed in any patient on the second treatment regime. In conclusion, immunosuppressant treatment based on cyclosporine could be safe and effective for KTRs diagnosed with COVID‐19. Abstract : Immunosuppression reduction alone, compared to immunosuppression reduction and maintenance of or conversion to low‐dose cyclosporine, was associated with less aggressive COVID‐19 disease in kidney transplant recipients.